2020
DOI: 10.3390/su12052083
|View full text |Cite
|
Sign up to set email alerts
|

China Railway Express Subsidy Model Based on Game Theory under “the Belt and Road” Initiative

Abstract: China Railway Express (CR Express) is an emerging freight transport mode between China and Europe, which provides a new option in addition to air transport and ocean shipping. At the initial stage of development, due to the higher freight costs compared to ocean shipping, the government subsidy provided for the China Railway Express operator plays an important role in the process of market cultivation. The original intention of the government subsidy was to promote the rapid and sustainable development of Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…China Railway Express has advantages over shipping by sea, especially in delivery time. It takes about 35 days on average to ship cargo by sea from China to Europe, while transport by land using China Railway Express takes one-third less time ( 10 , 11 ). Nevertheless, there are many problems with China Railway Express: lines and cargoes are not integrated ( 4 ); some trains operate with low cargo, while others are challenged by insufficient capacity ( 12 ); and non-uniform subsidy policies result in undercutting and disorderly competition ( 13 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…China Railway Express has advantages over shipping by sea, especially in delivery time. It takes about 35 days on average to ship cargo by sea from China to Europe, while transport by land using China Railway Express takes one-third less time ( 10 , 11 ). Nevertheless, there are many problems with China Railway Express: lines and cargoes are not integrated ( 4 ); some trains operate with low cargo, while others are challenged by insufficient capacity ( 12 ); and non-uniform subsidy policies result in undercutting and disorderly competition ( 13 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Seo et al ( 21 ) analyzed seven alternative routes for the export of laptop computers to Rotterdam, offering a method to select the route with the best transportation time and cost. Feng et al ( 11 ) found that China Railway Express can have larger benefits when transporting high-value cargoes. On the contrary, for low-value cargoes, government subsidies are necessitated for 30% of the transport costs ( 22 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To promote rail freight on the Belt and maintain normalised operation, operations of CR express under BRI are heavily subsidised (Bresharati et al , 2017; Qiwen and Xianliang, 2017; Jiang et al , 2018; Bucsky, 2019; Kundu and Sheu, 2019; Feng et al , 2020), varying from $US1,000 to 7,000 per FEU (Wang, 2015; Jiang et al , 2018).…”
Section: Background and Service Characteristicsmentioning
confidence: 99%
“…In response to the emergence of Eurasian rail freight, most research studies on Eurasian rail freight and the BRI are policy studies or consultancy work (Davydenko et al , 2012; UNECE, 2012, 2017; Rastogi and Arvis, 2014; Ardunio, 2016; Galushko, 2016; UIC and Roland Berger, 2017; Jakóbowski et al , 2018; Vinokurov et al , 2018). In addition to this, a rapidly increasing number of scholarly contributions deal with the competitiveness of container block train operations between China and Europe like Rodemann and Templar (2014), Besharati et al (2017), Chen et al (2017), Seo et al (2017), Yang et al (2018a, b), Wiegmans and Janic (2019), Jiang et al (2018, 2019), Wen et al (2019), Bucsky (2019), Dunmore et al (2019), Lu et al (2019), Kundu and Shen (2019) or Feng et al (2020) as well as some more in the Chinese language as discussed in Liu et al (2018) and Lee et al (2018). Other less related works are Song et al (2011), Song and Na (2012), Tsuji (2013) or Kim et al (2020) focusing on multimodal freight transports via Trans-Siberian Railway (TSR) with a short sea leg from China, South Korea and/or Japan to Russian Far East.…”
Section: Introductionmentioning
confidence: 99%
“…Physical barriers occur due to technical reasons such as varied railway systems (NIIAT, 2017), varied gauges (He, 2016), or scarce rolling stocks (Zhang & Schramm, 2018); inadequate or complete lack of infrastructure at a given link or node; and inability of handling a certain capacity or certain objects. Nonphysical obstacles negatively affect the quality of services, e.g., improper handling of cargo, transparency level of procedures, and policies (NIIAT, 2017); inefficient BCP Procedure (ESCAP, 2018) (CAREC, 2018); inconsistent custom regulations (Yan & Filimonov, 2018) (Jakóbowski,et al,218); border security (Haiquan, 2017) (Islam, et al, 2013); and shipment disparity (Leijen, 2019) (Feng et al, 2020). Apart from that, sustainability aspects, e.g., discussed in Sayyadi & Awasthi, 2018, Sayyadi & Awasthi, 2020, or Dubey et al, 2015 are not considered in this study, although they are relevant to the BRI discussion.…”
Section: Introductionmentioning
confidence: 99%